Fasted state bioavailability of two delayed release formulations of divalproex sodium in healthy Iranian volunteers - Parvin, Zakeri-Milani; Mahboob, Nemati; Saeed, Ghanbarzadeh; Hamed, Hamishehkar; Hadi, Valizadeh (Arzneimittelforschung, 2011)
The purpose of this study was to compare the pharmacokinetics and bioavailability of two commercial brands of delayed release divalproex sodium (CAS 76584-70-8) tablets in healthy male Iranian volunteers in fasted state. Each single-dose, randomized, open-label, blind study was conducted according to a crossover design in subjects. A washout interval of 14 days separated the doses in each study. Serial venous blood samples were obtained over 24 h after each administration to measure drug in serum, and placed into tubes containing sodium heparin. Then the separated plasma was kept frozen at −20 °C for subsequent analysis. The plasma concentrations of drug were analyzed by a validated sensitive HPLC method with UV detection. Mean maximum serum concentrations of 124.5 ± 34.8 μg/ml and 134.2 ± 31.1 μg/ml were obtained for the test and reference products, respectively. The and were 2023.8 ± 578.8 1 μg h/ml and 2705.3 ± 792.1 μg h/ml for the test and 2068.2 ± 526.4 μg h/ml and 2729.6 ± 698.2 μg h/ml for the reference formulation, respectively. The calculated 90% confidence intervals for the ratio of Cmax (87.2-101.5%), (92.1-108.6%) and (93.1 – 110.6%) values for the test and reference products were all within the 85-120% interval proposed by the FDA and EMA. Therefore the divalproex sodium tablets of the test and reference products are bioequivalent in terms of rate and extent of absorption.
Keywords: Bioavailability; Delayed release tablets; Divalproex sodium; Fasted state